Membangun Budaya Dialog, Menjadi Semakin Manusiawi Belajar dari Perspektif Personalisme Karol Wojtyla - Widyawan Louis, Aloysius (Fakultas Teologi, Universitas Sanata Dharma, 2024)
Diversity is convinced as one of the essential elements of the community, especially in Indonesia. The Indonesian had chosen Bhinneka Tunggal Ika as a slogan to build their unity for realizing their common good. Nevertheless, it is not easy to make a harmony in a multidiversity of Indonesia. The threat of segregation is increasingly strengthening along with the advances of information and communication technology which have a strong influence of capitalistic culture which tends to be pragmatic and individualistic. The rise in political contestation ahead of PEMILU 2024 also shows the strengthening of differentiation and separation of political identities and choices in Indonesian society from the grassroots to the government elites. Politics as a means for human beings to achieve a bonum commune which covers all aspects of human life in living together, is increasingly interpreted narrowly as a mere technique for seizing power. Living together, in society, as a nation and as a state is very likely to be further away from the ideals of Bhinneka Tunggal Ika, gotong royong, tepa selira, and other noble values that characterize our Indonesianness. Starting from this major threat Bhinneka Tunggal Ika, various efforts must be optimized to build new cultures of living together. It is very possible that these new cultures are a confirmation or strengthening of the Indonesian noble values which are believed to be deeply rooted in our national identity. One of the cultures that needs to be built is dialogue. In this paper, dialogue is generally understood as the interpersonal en-counters from different backgrounds who together want to be involved in some concrete efforts to achieve the common good. Karol Wojtyla's personalist perspective is used to un-derstand dialogue from its personalistic roots and how can probably be actualized to build a culture of dialogue in the context of Indonesia's diversity. In particular, it is a proof that Wojtyla's thoughts on dialogue were concretely real-ized throughout his pontificate as Pope John Paul II.AbstrakKeberagaman merupakan esensi hidup bersama, terlebih di Indonesia. Bhinneka Tunggal Ika dipilih sebagai semangat persatuan untuk mewujudkan cita-cita bersama. Meskipun demikian, tidak mudah membangun harmoni dalam kebe-ragaman. Ancaman segregasi semakin menguat bersamaan dengan kemajuan teknologi komunikasi dan informasi yang membawa pengaruh kuat budaya kapitalistik yang cenderung pragmatis dan individualistik. Maraknya kon-testasi politik menjelang PEMILU 2024 juga menampilkan menguatnya pembedaan dan pemisahan identitas dan pi-lihan politik mulai dari akar rumput sampai kalangan elit pemerintahan. Politik sebagai sarana manusia mencapai bonum commune yang mencakup seluruh aspek kehidu-pan manusia di dalam hidup bersama, semakin dimaknai secara sempit sebagai teknik merebut kekuasaan. Hidup bersama, bermasyarakat, berbangsa, dan bernegara sangat mungkin semakin jauh dari cita-cita Bhinneka Tunggal Ika, gotong royong, tepa selira, dan nilai-nilai luhur lain yang menjadi ciri ke-Indonesia-an kita. Bertitik tolak dari anca-man besar pada ke-bhinneka-tunggal-ika-an ini, berbagai upaya harus dimaksimalkan untuk membangun budaya-budaya baru dalam hidup bersama. Sangat mungkin sekali,budaya-budaya baru ini adalah peneguhan atau penguatan nilai-nilai luhur yang diyakini telah mengakar kuat dalam jati diri bangsa kita. Salah satu budaya yang perlu diban-gun adalah dialog. Dalam paper ini, dialog secara umum dimengerti sebagai perjumpaan interpersonal berlatarbe-lakang berbeda yang bersama-sama ingin terlibat dalam upaya mencapai kebaikan bersama. Perspektif personalis-me Karol Wojtyla digunakan untuk memahami dialog sampai akar-akar personalistiknya dan bagaimana mem-bangun budaya dialog itu dalam konteks keberagaman In-donesia. Secara istimewa, pemikiran Wojtyla tentang dialog diwujudnyatakannya secara konkret sepanjang masa ponti-fikalnya sebagai Paus Yohanes Paulus II.